Analisis Kesesuaian Akad Musyarakah Pada Program Balai Ternak Banjarjo Baznas Pacitan - Helmi Laila Azizah; Malta Anatyasari (Al-Musthofa: Journal of Sharia Economics, 2026)
This study investigates the applicability of the musyarakah contract in the Balai Ternak Banjarjo Program, which is managed by BAZNAS Pacitan. This is an essential issue since musyarakah is employed in a zakat-based livestock development program, along with Islamic financial institutions. The research employs a qualitative descriptive technique. The data were gathered through interviews, observations, and program documents, and then analyzed by comparing musyarakah practices to Islamic principles. The findings indicate that the musyarakah contract has been usually implemented in accordance with Islamic standards. BAZNAS offers funding, cattle, facilities, and mentorship, while members supply labor, cages, time, and livestock management. However, openness, reporting, administration, and oversight all require improvement. The study concludes that musyarakah may be used in zakat-based livestock empowerment programmes if justice, accountability, and transparency are maintained. The key consequence is that BAZNAS should tighten reporting and oversight in order to improve the program's adherence to Islamic values.